Pre-mortem: UnF.A.I.R - the Death of Open Research - KAN, Min-Yen (Institutional Knowledge at Singapore Management University, 2024)
Despite the calls for more open research by their proponents, adoption towards Open Research lags. Looking through the lens of a pre-mortem, we'll deconstruct the failure of a hypothetical open research project (in part in terms of F.A.I.R.-ness: Findable, Accessible, Interoperable and Reusable) and take away how to design open research for better success.